Michelle Smith's Full Stroke at 15 m into the Crawl Stroke Leg of Her 200 m Individual Medley Gold Medal Race at the Atlanta Olympic Games 1996 - Rushall, B. S.
Video pictures (18 frames) and the appropriate technical/ biomechanical explanations for Michelle Smith's full stroke at 15 m into the crawl stroke Leg of her 200 m individual medley gold medal race at the Atlanta Olympic Games 1996. There are certain features of this stroke that make it understandable why Michelle Smith is an Olympic champion. Her pull is well under the body in its latter stages. This minimizes excessive lateral dissipation of force. All the musculature of the shoulders, the internal rotator muscles (anterior deltoid, pectoralis major, latissimus dorsi) and the external rotator muscles (infraspinatus, teres minor, supraspinatus) are used to perform a very vigorous and powerful underwater pull. On both arms the external rotators are emphasized more than the internal rotators. Shoulder rotation places the swimmer's anatomy into a good position. The head is well down which promotes high hips and therefore, good streamlining. Strong adduction provides power to the hand/forearm propulsive surface to produce a "long" propulsive phase in the underwater movement.